2011
DOI: 10.1371/journal.pone.0024151
|View full text |Cite
|
Sign up to set email alerts
|

LUMP Is a Putative Double-Stranded RNA Binding Protein Required for Male Fertility in Drosophila melanogaster

Abstract: In animals, male fertility requires the successful development of motile sperm. During Drosophila melanogaster spermatogenesis, 64 interconnected spermatids descended from a single germline stem cell are resolved into motile sperm in a process termed individualization. Here we identify a putative double-stranded RNA binding protein LUMP that is required for male fertility. lump1 mutants are male-sterile and lack motile sperm due to defects in sperm individualization. We show that one dsRNA binding domains (dsR… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
22
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 12 publications
(24 citation statements)
references
References 44 publications
2
22
0
Order By: Relevance
“…80 Recently, it was found that genetic perturbation of the RNAi pathway causes individualization phenotypes. [81][82][83] RNAi pathway mutations also perturb cytoskeletal reorganization of the oocyte in a checkpointmediated process. 84 This seems to be a way for the oocyte to abort development when chromosomal integrity is disturbed by unregulated transposon activity.…”
mentioning
confidence: 99%
“…80 Recently, it was found that genetic perturbation of the RNAi pathway causes individualization phenotypes. [81][82][83] RNAi pathway mutations also perturb cytoskeletal reorganization of the oocyte in a checkpointmediated process. 84 This seems to be a way for the oocyte to abort development when chromosomal integrity is disturbed by unregulated transposon activity.…”
mentioning
confidence: 99%
“…Individualization has been extensively studied in Drosophila , and many genes are involved in this process, including lump , myosinVI , auxilin and npc1 (Hicks et al, 1999; Zhou et al, 2007; Sanders and Smith, 2011; Wang et al, 2011). From these studies, actin assembly, apoptosis, and membrane trafficking become the three best understood processes shown to affect different aspects of sperm maturation.…”
Section: Discussionmentioning
confidence: 99%
“…Spermatogenesis involves a series of tightly regulated stages including mitotic proliferation, meiotic division, and cellular remodeling (Sanders and Smith, 2011). The adult Drosophila testis is a bipolar tube-like structure.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations